Health risk assessment through probabilistic sensitivity analysis of carbon monoxide and fine particulate transportation exposure - E. Ernyasih; A. Mallongi; A. Daud; S. Palutturi; S. Stang; R. Thaha; E. Ibrahim; W. Al Madhoun (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The rising number of vehicles used for transportation, which is attributed to the steady increase in population, is known to be a major contributor of air pollution, which, in turn, can have adverse effects on the environment and human health. Therefore, in this study, we aimed to evaluate the concentration of carbon monoxide and fine particulate matter in the air and their potential health risks and further examine the use of probabilistic methods to simulate the sensitivity of people living in communities and school children to these pollutants.METHODS: This study collected carbon monoxide and fine particulate matter samples from 32 stations near community houses and 14 sites near schools located along roads. Hazard quotient and target hazard quotient calculations were used to estimate the non-carcinogenic health risks associated with exposure to these substances for both community adults and school children. Finally, Monte Carlo simulations were applied to analyze the sensitivity and uncertainty risks.   FINDINGS: As per the results, the highest level of carbon monoxide was recorded in station 22, with 6729 microgram per cubic meter, while the lowest was in station 24, with 1037 microgram per cubic meter. Station 10 had the highest concentration of fine particulate matter at 116 microgram per cubic meter, as opposed to station 2 with the lowest level at 10 microgram per cubic meter. In children, the hazard quotient value for carbon monoxide was found to be highest at 3.013, with the lowest at 0.614. Similarly, the highest level of target hazard quotient for carbon monoxide in children was 7.370, whereas the lowest was 1.522. For fine particulate matter, the highest risk level was 0.180. Additionally, the highest, and lowest levels of target hazard quotient for fine particulate matter were 0.311 and 0.037, respectively. Deterministic and probabilistic approaches were used to assess the risks these pollutants impose on adults and school children based on their daily inhalation rate. The results revealed that the 5th and 95th percentiles of cancer risk for carbon monoxide in adults were 2.85 and 6.11, respectively, indicating medium risks. However, for fine particulate matter, the 5th, and 95th percentiles were 0.09 and 0.19, respectively, signifying lower risks. For school children, the percentiles for carbon monoxide and fine particulate matter were 1.20 and 2.50, respectively, demonstrating higher risks.CONCLUSION: As per the results, it was determined that the hazard quotient risk for carbon monoxide in adults exceeded the standard, >1, thus posing a risk. Only three stations had hazard quotient values lower than 1, which is deemed of safe level. Most of the fine particulate matter risk assessment results had hazard quotient values lower than 1, indicating a safe level. However, all other 30 stations had exceeded the World Health Organization standard (>1), thus demonstrating risks. The likelihood of the inhabitants being at risk increased as the frequency of discrete exposure occurrences increased; this is evidenced by target hazard quotient calculation results for both carbon monoxide and fine particulate matter at the 32 monitored station areas. These results warrant that future research should focus on reducing carbon monoxide and fine particulate matter in the environment by fostering awareness among local and national stakeholders as well as the academe; this may allow South Tangerang to become a center of excellence for green schools in the area.